Keep calm, but watch the outliers: Deposit flows in recent crisis episodes and beyond - Luisa Fascione; Koen Oosterhek; Beatrice Scheubel; Livio Stracca; Nadya Wildmann (European Central Bank (ECB), 2024)
Since the March 2023 banking turmoil, a policy debate has emerged concerning the unprecedented scale and speed of the observed deposit outflows. Have recent stress episodes and developments in technology structurally changed depositors' behaviour? Are the Basel III liquidity coverage ratio (LCR) run-off assumptions for cash outflows still fit for purpose? Leveraging on monthly liquidity reporting for a sample of 110 significant institutions (SIs) between 2016 and 2024, we shed light on some stylised facts pertaining to the composition of deposit flows in the banking union. Overall, we find limited evidence of a structural change in the statistical behaviour of deposit flows to date. For all but one of the deposit classes included in the analysis, more than 90% of observable net outflows remained below the LCR run-off assumptions during the whole sample period. Some extreme deposit outflows recorded during the COVID-19 pandemic and for a few SIs assessed as failing or likely to fail (FOLTF) remain rare tail events for which the LCR standard was not designed.
Keywords: G20; G21; G28; 330; liquidity risk; deposit outflows; bank runs; LCR run-off assumptions; bank regulation; financial risk; banking policy; financial institution; monetary crisis